Solitary Contralateral Adrenal Metastases after Nephrectomy for Renal Cell Carcinoma - Nikolaos Antoniou; Demetrios Karanastasis (The Scientific World Journal)
Two cases are reported of patients with a single metastasis in the contralateral adrenal, one and nine years respectively after nephrectomy for localized cancer in the opposite kidney. These types of metastases are usually asymptomatic they do not appear with signs of adrenal insufficiency, they are detected incidentally and the diagnosis is confirmed mainly with CT scan, which comprises the method of choice for the detection of such types of metastases. Many adrenal metastases probably have been overlooked in the past when advanced imaging techniques were not available. Both patients underwent adrenalectomy and replacement therapy with corticosteroids. Approximately 50% of all patients with renal cell carcinoma either present with metastases at diagnosis or will have metastatic disease after nephrectomy11. In order of decreasing frequency, the most common metastatic sites are the lungs, lymph nodes, liver, bone, contralateral kidney and ipsilateral adrenal glands. Adrenal involvement has been reported in 7 to 19% of autopsystudies. 1,3 Solitary metachronous metastatic involvement of the contralateral adrenal from renal cell carcinoma is rarely diagnosed during life and only 4 cases have been reported. 4,5 Recent advances in imaging techniques have allowed the diagnosis of adrenal involvement by renal cancer. Two cases of contralateral adrenal metastasis are reported 1 and 9 years after radical nephrectomy for localized renal cell carcinoma. Both patients underwent adrenalectomy and steroid replacement therapy.